Implementation of the Concept of I'tibar Al Ma'alat in Sharia Banks Toward Customer Late Fines for Delaying Payment Obligations - Aminuddin, Aminuddin; Puspa Devi, Chindya Pratisti (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2024)
The concept of I'tibar Al Ma'alat is a legal consideration that is carried out based on the participation or understanding of a guideline study and sees its relationship with the consequences that occur, be it good or bad consequences. This study aims to determine the principle of I'tibar Al Ma'alat, the rules and regulations of Islamic banks related to fines on customers who are late in paying obligations to be in line with the concept of I'tibar Al Ma'alat and the impact of the implementation of the concept of I'tibar Al Ma'alat in terms of fines on customers and Islamic banks. This research uses a qualitative method with a normative juridical approach by extrapolating the legal texts set to consider the results with data collection through library research by reading and analysing in the form of fatwa books of DSN-MUI scholars, laws. The findings in this study indicate that the concept of I'tibar Al Ma'alat in the form of the bank continues to impose fines in the bank's internal system with the opportunity for customers to appeal the imposition of fines accompanied by evidence of force majeure faced with a certain period of time. The principle of I'tibar Al Ma'alat provides a solution that is more valuable, just and beneficial in accordance with the objectives of Maqashid Sharia.